2012
DOI: 10.1177/0095798411431981
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation Style and Alcohol Use Among African American College Students

Abstract: This study examined whether a relationship exists between acculturation and alcohol use among African American college students and if the relationship varies by religiosity and gender. Most researchers use unidimensional African American acculturation measures that cannot capture the construct's complexity; this study is the first to use a bidimensional measure. Results revealed a relationship between acculturation and alcohol use. Less frequent drinking occurred among marginalists (those who reject both Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Consistent with the findings of Abdullah and Brown (2012) and Witbrodt, Mulia, Zemore, & Kerr (2014), this study provides additional evidence of the deleterious relationships between racism, discrimination, and acculturative stress on negative health behaviors (Dion, 2001;Harrell, Merritt, & Kalu, 1998;Krieger, 1999;Rollock & Gordon, 2000;Williams & Williams-Morris, 2000); extending this work to include risky alcohol use behaviors among Black college students. When considered independently, both race-related stress and acculturative stressors were positively associated with risky alcohol use and coping motivated drinking behaviors in Black college students.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the findings of Abdullah and Brown (2012) and Witbrodt, Mulia, Zemore, & Kerr (2014), this study provides additional evidence of the deleterious relationships between racism, discrimination, and acculturative stress on negative health behaviors (Dion, 2001;Harrell, Merritt, & Kalu, 1998;Krieger, 1999;Rollock & Gordon, 2000;Williams & Williams-Morris, 2000); extending this work to include risky alcohol use behaviors among Black college students. When considered independently, both race-related stress and acculturative stressors were positively associated with risky alcohol use and coping motivated drinking behaviors in Black college students.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, Blue and Berkel (2010) suggested that African American college students may internalize the dominant culture's views of body type and thinness, which may lead them to experience greater body dissatisfaction and disordered eating patterns. Previous research has also shown that self-esteem and acculturation moderate the association between alcohol use and body image perception for African Americans (Abdullah & Brown, 2012). Thus, there may be acculturation and assimilation issues that may lead to psychological distress (e.g., anxiety, low self-esteem, poor body image; Blue & Berkel, 2010), and this psychological distress may then be exhibited in disordered eating behaviors, alcohol use, or other risky behaviors among African American college women.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers have also observed a link between alcohol abuse and acculturation among African Americans. For example, Abdullah and Brown (2012) used a bidirectional framework of acculturation and examined its relation to alcohol use among African American college students. Students who utilized a marginal acculturation strategy (i.e., those who rejected both African American and mainstream culture) reported less frequent drinking, while students with an assimilationist acculturative strategy (i.e., those who rejected African American culture in favor of mainstream culture) drank more frequently.…”
Section: Acculturationmentioning
confidence: 99%